Struktur Komunitas Zooplankton di Sungai Namu Sira-Sira Desa Durian Lingga Kabupaten Langkat Sumatera Utara - Eka Silvia; Melfa Aisyah Hutasuhut (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the structure of the zooplankton community in the Namu Sira-Sira River, located in Durian Lingga Village, Langkat Regency, North Sumatra. A descriptive-explorative method was employed using purposive random sampling at three stations, with each station sampled three times. The results showed the presence of 9 zooplankton species belonging to 9 families and 6 orders, with a total of 1277 individuals. The most dominant species identified was Euglypha sp., with 280 individuals, while the least abundant was Nauplius sp., with 14 individuals. In conclusion, the zooplankton community structure in the Namu Sira-Sira River indicates that the aquatic environment is healthy and stable, supporting the survival and development of the zooplankton community. Keywords: Community Structure, Namu Sira-Sira River, Water Quality, Zooplankton.